2012
DOI: 10.1210/jc.2011-1935
|View full text |Cite
|
Sign up to set email alerts
|

Hypercalcemia, Hypercalciuria, and Elevated Calcitriol Concentrations with Autosomal Dominant Transmission Due toCYP24A1Mutations: Effects of Ketoconazole Therapy

Abstract: In a syndrome characterized by intermittent hypercalcemia, hypercalciuria, elevated 1,25-dihydroxyvitamin D, undetectable 24,25-dihydroxyvitamin D concentrations, splice junction mutations of the CYP24A1 gene, and autosomal dominant transmission of the trait, treatment with ketoconazole is useful in reducing urinary calcium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
102
0
10

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 172 publications
(122 citation statements)
references
References 18 publications
6
102
0
10
Order By: Relevance
“…In summary, our results show that increased 25(OH)D/24,25(OH) 2 D supports the diagnosis of reduced CYP24A1 activity in patients with mutations of the CYP24A1 gene (12,13 ). 25(OH)D/24,25(OH) 2 D Ն99 in a patient with hypercalcemia of unknown etiology warrants genetic confirmation.…”
Section: Participants and Samplessupporting
confidence: 62%
See 2 more Smart Citations
“…In summary, our results show that increased 25(OH)D/24,25(OH) 2 D supports the diagnosis of reduced CYP24A1 activity in patients with mutations of the CYP24A1 gene (12,13 ). 25(OH)D/24,25(OH) 2 D Ն99 in a patient with hypercalcemia of unknown etiology warrants genetic confirmation.…”
Section: Participants and Samplessupporting
confidence: 62%
“…Depending on calcium and phosphorus demands, D (10, 11 ). Inactivating mutations of CYP24A1 (cytochrome P450, family 24, subfamily A, polypeptide 1) cause hypercalcemia, hypercalciuria, and increased 1,25(OH) 2 D concentrations (12)(13)(14)(15)(16)(17)(18)(19)(20). In studies describing LC-MS/MS assays for 24,25(OH) 2 D quantification, the relationship between 25(OH)D and 24,25(OH) 2 D has been used as a nutritional marker for assessment of optimum vitamin D supplementation (21 ).…”
Section: Hydroxyvitamin D [25(oh)d]mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have identified mutations in CYP24A1 to be a novel cause of hypercalcaemia 13,20,21 . Currently, more than 10 loss-of-function mutations in CYP24A1 have been described with this phenotype, supported by evidence of in vitro and in vivo loss of enzyme function.…”
Section: Discussionmentioning
confidence: 99%
“…Several findings suggest that they could. First, the pedigree described by Tebben et al 21 includes an adult (detailed above) with active renal stone disease, who was asymptomatic throughout childhood. Second, in response to the initial report describing CYP24A1 mutations in idiopathic infantile hypercalcaemia 13 , Streeten et al describe an adult patient with hypercalcaemia, nephrolithiasis and bone disease who was found to have a homozygous mutation in CYP24A1.…”
Section: Discussionmentioning
confidence: 99%